2021
DOI: 10.1007/s10067-020-05550-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 arthritis: a case report and literature review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) is the novel pathogen responsible for the coronavirus disease 19 (COVID-19) outbreak. Researchers and clinicians are exploring the pathogenetic mechanisms of the viral-induced damage and growing interest is focusing on the short-term and long-term immune-mediated consequences triggered by the infection. We will focus on post-SARS-CoV2 infection arthritis which may arise as a new pathological condition associated with COVID-19. In this article, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
1
14

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(119 citation statements)
references
References 29 publications
2
94
1
14
Order By: Relevance
“…However, due to the heterogeneity of randomized controlled trials (RCTs) design and cohorts, and the presence of limitations, as for example concomitant steroidal treatment, studies have showed mixed results on the impact of these therapies on COVID-19 outcomes [7,8]. Many questions remain still open and one of the most important is whether patients with autoimmune arthropathies and autoinflammatory disorders may have different responses to the SARS-CoV-2 infection, because of impaired immunological and genetic background and/or concomitant antirheumatic treatment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the heterogeneity of randomized controlled trials (RCTs) design and cohorts, and the presence of limitations, as for example concomitant steroidal treatment, studies have showed mixed results on the impact of these therapies on COVID-19 outcomes [7,8]. Many questions remain still open and one of the most important is whether patients with autoimmune arthropathies and autoinflammatory disorders may have different responses to the SARS-CoV-2 infection, because of impaired immunological and genetic background and/or concomitant antirheumatic treatment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…3 Consistent with these premises, from the earliest phases of the pandemic, inflammatory musculoskeletal manifestations following COVID-19 have been described in isolated case reports although no systematically collected cohorts are still available to unveil the clinical spectrum of post-COVID-19 arthritis. 4 To contribute to shed light on this field, in December 2020, we built a web-based survey platform and invited all members of our study group to submit cases of inflammatory joint disease and onset within 8 weeks from a confirmed SARS-CoV-2 infection (demonstrated either by reverse transcription PCR on nasopharyngeal swab or SARS-CoV-2specific IgM antibodies) encountered during routine clinical practice from 31 January 2020 and up to 31 March 2021. Exclusion criteria were a history of any inflammatory rheumatic disease or psoriasis.…”
mentioning
confidence: 99%
“…Arthrocentesis revealed the inflammatory nature of synovial fluid [12]. Progressive nature of the arthritis and absence of affection of joints other than the hip makes our case unique.…”
Section: Post-covid-19 Inflammatory Arthritismentioning
confidence: 76%